Temporal trends in treatment and survival of older adult diffuse large B-Cell lymphoma patients in the SEER-Medicare linked database. Issue 13 (10th November 2019) - Shaw, Jaime; Harvey, Christopher; Richards, Catherine; Kim, Christopher
Abstract: To describe temporal trends in treatment among older adult (≥66 years) patients diagnosed with diffuse large B-cell lymphoma (DLBCL), we analyzed 18, 058 DLBCL patients from the Surveillance, Epidemiology, and End Results linked Medicare (SEER-Medicare) database diagnosed between 2001 and 2013. Among 65% of patients receiving treatment after diagnosis, R-CHOP (Rituximab, Cyclophosphamide, Doxorubicin, Vincristine, Prednisone) was the most common frontline therapy, increasing with more recent treatment year: 51% (2001–2003) vs. 69% (2010–2014). Autologous and allogeneic hematopoietic stem cell transplantation (HSCT) was uncommon in these Medicare patients. As the addition of rituximab increased over time, we also observed an improved survival rate over time. It is possible there is an association, but we cannot make this inference as effectiveness was not measured in this study. Overall survival estimates indicated that survival probabilities steadily improved in more recent years; however, 5-year survival was <40%, indicating the need for improved treatment options for older adult DLBCL patients.